Dogs as Reservoirs for Leishmania donovani, Bihar, India, 2018–2022 - Anurag Kumar Kushwaha; Ashish Shukla; Breanna M. Scorza; Rahul Chaubey; Dharmendra Kumar Maurya; Tulika Kumari Rai; Shyamali Yaduvanshi; Shweta Srivastava; Gaetano Oliva; Epke A. Le Rutte; Rajiv Kumar; Om Prakash Singh; et al. (Emerging Infectious Diseases)
Visceral leishmaniasis derived from Leishmania donovani is transmitted by sand flies (Phlebotomus argentipes) throughout the Indian subcontinent. Although considered anthroponotic, L. donovani infects other mammals susceptible to sand fly bites, including dogs. Aggressive strategies to reduce sand fly populations in India have led to flies seeking nonhuman hosts, so understanding the role of dogs in L. donovani transmission has become critical. Our study investigated L. donovani infection in dogs and the potential for such infections to be transmitted back to sand flies. We performed xenodiagnosis by using P. argentipes on dogs (n = 73) with quantitative PCR–detectible parasitemia in both endemic and outbreak villages. We found that 12% (9/73) of dogs were infectious to sand flies during winter and rainy seasons. Patients with visceral leishmaniasis remain primary sources of L. donovani transmission, but our findings suggest a possible link between canine infection and human exposure.